Těsnící podzemní stěny - Kaderka, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Tématem této práce je historie, účel provádění podzemních těsnících stěn, typy používaných technologií a konkrétní příklady jejich využití v praxi. Část práce se bude věnovat parametrům pojiv a injektážních směsí.

The topic of this thesis is history, the purpose to carry out diaphragm wall, types of the emplyoed technologies and specific examples of its application in practise. Part of this thesis will concantrate on the parametres of bonding agents and the grouting mixtures.
Sealing Diaphragm Walls
Keywords: podzemní těsnící stěny; technologie; suspenze; diaphragm walls; technologies; suspenzion